Classification of Ancient Egyptian Astronomical 'Diagrams'. (February 2015) - Symons, Sarah
The diverse group of 81 numbered 'monuments' in Neugebauer and Parker's Egyptian Astronomical Texts, Volume 3 represents a collection of several different types of document. Arranged chronologically from the Middle Kingdom (c. 2000 B.C.) to the Roman Period (second century A.D.), these texts are more difficult to analyse than when grouped into traditions. Neugebauer and Parker's system of families presented one basis for classification. This paper presents a second, complementary, way of looking at the documents, with the aim of opening up the possibilities for further analysis of the relationships between the texts and the modes of information transmission for the astronomical information they contain.